Implantable flexible pressure measurement system based on inductive coupling - Oliveira, Cristina C. (2015)
One of the currently available treatments for aortic aneurysms is endovascular aneurysm repair (EVAR). In spite of major advances in the operating techniques, complications still occur and lifelong surveillance is recommended. In order to reduce and even eliminate the commonly used surveillance imaging exams, as well as to reduce follow-up costs, new technological solutions are being pursued. In this paper, we describe the development, including design and performance characterization, of a flexible remote pressure measurement system based on inductive-coupling for post-EVAR monitoring purposes. The telemetry system architecture and operation are described and main performance characteristics discussed. The implantable sensor details are provided and its model is presented. Simulations with the reading circuit and the sensor's model were performed and compared with measurements carried out with air and a phantom as media, in order to characterize the telemetry system and validate the models. The transfer characteristic curve (pressure versus frequency) of the monitoring system was obtained with measurements performed with the sensor inside a controlled pressure vacuum chamber. Additional experimental results which proof the system functionality were obtained within a hydraulic test bench that emulates the aorta. Several innovative aspects, when compared to the state of the art, both in the sensor and in the telemetry system were achieved.